Outsourcing informatyczny a zarządzanie wiedzą - Sobińska, Małgorzata (The Knowledge Management and Outsourcing, 2005)
The aim of the article is to show outsourcing as one of the ways of using outside knowledge. It shows the specificity of IT personnel work. It stresses the role of proper knowledge transfer between cooperating companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 248-255